31P NMR Evidence for Peroxide Intermediates in Lipid Emulsion Photooxidations: Phosphine Substituent Effects in Trapping. (4th September 2017) - Mohapatra, Prabhu P.; Chiemezie, Callistus O.; Kligman, Arina; Kim, Michele M.; Busch, Theresa M.; Zhu, Timothy C.; Greer, Alexander
Abstract: Intralipid is a lipid emulsion used in photodynamic therapy (PDT) for its light scattering and tissue‐simulating properties. The purpose of this study is to determine whether or not Intralipid undergoes photooxidation, and we have carried out an Intralipid peroxide trapping study using a series of phosphines [2′‐dicyclohexylphosphino‐2, 6‐dimethoxy‐1, 1′‐biphenyl‐3‐sulfonate, 3‐(diphenylphosphino)benzenesulfonate, triphenylphosphine‐3, 3′, 3′′‐trisulfonate and triphenylphosphine]. Our new findings are as follows: (1) An oxygen atom is transferred from Intralipid peroxide to the phosphine traps in the dark, after the photooxidation of Intralipid. 3‐(Diphenylphosphino)benzenesulfonate is the most suitable trap in the series owing to a balance of nucleophilicity and water solubility. (2) Phosphine trapping and monitoring by 31 P NMR are effective in quantifying the peroxides in H2 O. An advantage of the technique is that peroxides are detected in H2 O; deuterated NMR solvents are not required. (3) The percent yield of the peroxides increased linearly with the increase in fluence from 45 to 180 J cm −2 based on our trapping experiments. (4) The photooxidation yields quantitated by the phosphines and 31 P NMR are supported by the direct 1 H NMR detection using deuterated NMR solvents. These data provide the first steps in the development of Intralipid peroxide quantitation after PDT using phosphine trapping and 31 P NMR spectroscopy. Abstract : Phosphines are shown to be efficient trapping agents for peroxides in postphotooxidation/photoreactions of Intralipid.